BCG vaccination in England since 2005: a survey of policy and practice. Issue 5 (10th September 2012) - Pilger, Daniel; Nguipdop-Djomo, Patrick; Abubakar, Ibrahim; Elliman, David; Rodrigues, Laura C; Watson, John M; Eastman, Vera; Mangtani, Punam
Abstract : Objective: Assess the current BCG vaccination policies and delivery pathways for immunisation in Primary Care Trusts (PCTs) in England since the 2005 change in recommendations. Design: A survey of key informants across PCTs using a standardised, structured questionnaire. Setting: 152 PCTs in England. Results: Complete questionnaires were returned from 127 (84%) PCTs. Sixteen (27%) PCTs reported universal infant vaccination and 111 (73%) had selective infant vaccination. Selective vaccination outside infancy was also reported from 94 (74%) PCTs. PCTs with selective infant policy most frequently vaccinated on postnatal wards (51/102, 50%), whereas PCTs with universal infant vaccination most frequently vaccinated in community clinics (9/13, 69%; p=0.011). To identify and flag up eligible infants in PCTs with targeted infant immunisation, those who mostly vaccinate on postnatal wards depend on midwives and maternity records, whereas those who vaccinate primarily in the community rely more often on various healthcare professionals. Conclusions: Targeted infant vaccination has been implemented in most PCTs across the UK. PCTs with selective infant vaccination provide BCG vaccine via a greater variety of healthcare professionals than those with universal infant vaccination policies. Data on vaccine coverage would help evaluate the effectiveness of delivery. Interruptions of delivery noted here emphasise the importance of not just an agreed, standardised, local pathway, but also a named person in charge.